2 $×$ 2 MIMO FBMC-OQAM Signal Transmission Over a Seamless Fiber–Wireless System in the W-band - Francois Rottenberg; Pham Tien Dat; Trung-Hien Nguyen; Atsushi Kanno; Francois Horlin; Jerome Louveaux; Naokatsu Yamamoto (IEEE Photonics Journal)
Offset-QAM-based filterbank multicarrier (FBMC-OQAM) is an attractive modulation candidate to increase the spectral efficiency of radio-over-fiber and fiber–wireless systems. In this paper, we first propose a general framework for MIMO FBMC-OQAM transmission systems, including the description of algorithms for mitigation of the channel impairments. The proposed design is scalable in the number of transmitted streams and flexible as multiple asynchronous users can be accommodated. The proposed system is experimentally validated in a 2 $×$ 2 MIMO FBMC-OQAM signal over a seamless fiber–wireless in the W-band for the first time. Satisfactory performance is confirmed for a data rate of up to 18 Gb/s in both downlink and uplink directions. Furthermore, algorithms previously proposed by the authors for channel estimation and phase noise compensation are experimentally validated, confirming their effectiveness. Finally, we show that, for a similar error vector magnitude performance, an FBMC-OQAM system can achieve a 25% higher throughput rate than a corresponding orthogonal frequency division multiplexing-based fiber–wireless system.